Abnormal spinopelvic mobility as a risk factor for acetabular placement error in total hip arthroplasty using optical computer- assisted surgical navigation system. (2022) - Jang, S. J.; Vigdorchik, J. M.; Windsor, E. W.; Schwarzkopf, R.; Mayman, D. J.; Sculco, P. K.
No abstract available